Effect Of Electron Beam Irradiation Of High Density Polyethylenewaste Tire Powder (Hdpewtp) Blends On Processability, Tensile Properties And Morphological Properties - Azami, Khairunnisa Azalin (Universiti Sains Malaysia, 2018)
Recycling of waste is still a current issue. Saving primary sources and energy should be a priority. Inexpensive recycling which is environmentally friendly should be preferred. Nowadays, the rubber industry and the consumption of polymeric materials increase in parallel to the rapid industrialization and civilization. As polymeric materials do not decompose easily, disposal of waste polymers is a major environmental problem.Other than that, the improvement of the toughness of HDPE also need to be studied. In order to recycle the waste and improve the properties of HDPE, HDPE was blended with WTP and EB irradiation was conducted. The waste tire selected was in powder form and sieved to get smaller size than 3 micron. It acts as filler while the high density polyethylene acts as matrix. The fillers content were varied which are 0, 1, 2, 3 and 5 percent. Electron beam irradiation was conducted to study the differences behaviour of the blends under radiation treated and without radiation treated. Processability monitoring, tensile test and failure analysis were carried out to investigate the properties of the blends. Overall, the results show that the varied content of fillers affected the processability, tensile properties and morphology of the blends. The radiation treatment had also improved the properties of the blends.